Analysis of stamping cracking of laser tailor-welded IF steel door inner plate. Issue 1 (1st December 2022) - Xian, Lingbiao; Wu, Ke; Li, Liejun
Abstract: The parts produced by laser tailor welded steel plates are more and more widely used in automobiles, due to their advantages of high strength, low weight, and low comprehensive cost. However, the welding seam of the laser tailor welded steel plate is prone to cracking during the stamping process. Based on solving the problem of stamping cracking of the IF steel door inner plate supplied by our company, the mechanical properties and friction coefficient were tested on the base metal. In addition, the cupping experiment was carried out on the weld seam of the tailor-welded blanks, and the hardness and microstructure of the weld seam were also tested and analyzed. The results showed that the lap height difference was the main reason for cracking. By optimizing the height difference of tailor-welded blanks, the incidence of cracking was greatly reduced.